Alpha-particle irradiation effects on uranium-bearing Gd2Zr2O7 ceramics for nuclear waste forms. Issue 2 (February 2017) - Shu, Xiaoyan; Fan, Long; Xie, Yi; Zhu, Weidong; Pan, Sheqi; Ding, Yi; Chi, Fangting; Wu, Yanlin; Lu, Xirui
Abstract: It is necessary to study the self-irradiation effects of nuclear waste forms under α-decay in the long term storage. In the present work, accelerated irradiation experiments were performed on (Gd1-4 x U2 x )2 (Zr1- x U x )2 O7 ( x  = 0, 0.10, 0.14) samples using 0.5 MeV alpha-particle irradiation at fluences ranging from 1 × 10 14 to 1 × 10 17  ions/cm 2 at room temperature. Irradiation induced microstructural evolution was examined by grazing incidence X-ray diffraction (GIXRD), Raman spectroscopy and Field-emission scanning electron microscopy (FESEM). The results show that the main crystal structure is kept, however, weaker structural ordering is leaded as a result of intensified irradiation. And the radiation resistance is enhanced by the growing uranium content in the discussed range. Moreover, the irradiation effects as a function of depth have been discussed. Raman spectra reveal that the vibration intensity of atomic bonds are changed due to increased irradiation. In addition, the microtopography and element distribution have been kept after irradiation.